Efficacy and Safety of, and Patient Satisfaction with, Colonoscopic-Administered Fecal Microbiota Transplantation in Relapsing and Refractory Community- and Hospital-Acquired Clostridium difficile Infection - Muhammad Ali Khan; Aijaz Ahmed Sofi; Usman Ahmad; Osama Alaradi; Abdur Rahman Khan; Tariq Hammad; Jennifer Pratt; Thomas Sodeman; William Sodeman; Sehrish Kamal; Ali Nawras (Canadian Journal of Gastroenterology and Hepatology)
OBJECTIVE: To report the efficacy and safety of, and patient satisfaction with, colonoscopic fecal microbiota transplantation (FMT) for community- and hospital-acquired Clostridium difficile infection (CDI).